Characterization of an organic semiconductor diode for dosimetry in radiotherapy. Issue 8 (3rd June 2020) - Posar, Jessie A.; Davis, Jeremy; Large, Matthew J.; Basiricò, Laura; Ciavatti, Andrea; Fraboni, Beatrice; Dhez, Olivier; Wilkinson, Dean; Sellin, Paul J.; Griffith, Matthew J.; Lerch, Michael L. F.; Rosenfeld, Anatoly; et al.
Abstract : Purpose: The development of novel detectors for dosimetry in advanced radiotherapy modalities requires materials that have a water equivalent response to ionizing radiation such that characterization of radiation beams can be performed without the need for complex calibration procedures and correction factors. Organic semiconductors are potentially an ideal technology in fabricating devices for dosimetry due to tissue equivalence, mechanical flexibility, and relatively cheap manufacturing cost. The response of a commercial organic photodetector (OPD), coupled to a plastic scintillator, to ionizing radiation from a linear accelerator and orthovoltage x‐ray tube has been characterized to assess its potential as a dosimeter for radiotherapy. The radiation hardness of the OPD has also been investigated to demonstrate its longevity for such applications. Methods: Radiation hardness measurements were achieved by observing the response of the OPD to the visible spectrum and 70 keV x rays after pre‐exposure to 40 kGy of ionizing radiation. The response of a preirradiated OPD to 6‐MV photons from a linear accelerator in reference conditions was compared to a nonirradiated OPD with respect to direct and indirect (RP400 plastic scintillator) detection mechanisms. Dose rate dependence of the OPD was measured by varying the surface‐to‐source distance between 90 and 300 cm. Energy dependence was characterized from 29.5 to 129 keV with an x‐ray tube. The percentage depth dose (PDD) curves were measured from 0.5 to 20 cm and compared to an ionization chamber. Results: The OPD sensitivity to visible light showed substantial degradation of the broad 450 to 600 nm peak from the donor after irradiation to 40 kGy. After irradiation, the spectral shape has a dominant absorbance peak at 370 nm, as the acceptor better withstood radiation damage. Its response to x rays stabilized to 30% after 35 kGy, with a 0.5% difference between 770 Gy increments. The OPD exhibited reproducible detection of ionizing radiation when coupled with a scintillator. Indirect detection showed a linear response from 25 to 500 cGy and constant response to dose rates from 0.31 Gy/pulse to 3.4 × 10 −4  Gy/pulse. However, without the scintillator, response increased by 100% at low dose rates. Energy independence between 100 keV and 1.2 MeV advocates their use as a dosimeter without beam correction factors. A dependence on the scintillator thickness used during a comparison of the PDD to the ionizing chamber was identified. A 1‐mm‐thick scintillator coupled with the OPD demonstrated the best agreement of ± 3%. Conclusions: The response of OPDs to ionizing radiation has been characterized, showing promising use as a dosimeter when coupled with a plastic scintillator. The mechanisms of charge transport and trapping within organic materials varies for visible and ionizing radiation, due to differing properties for direct and indirect detection mechanisms and observing a substantial decrease in sensitivity to the visible spectrum after 40 kGy. This study proved that OPDs produce a stable response to 6‐MV photons, and with a deeper understanding of the charge transport mechanisms due to exposure to ionizing radiation, they are promising candidates as the first flexible, water equivalent, real‐time dosimeter.